Initial development and validity evidence for the processes of change in Psychological Skills Training Questionnaire - Massey, M. V.; Meyer, B. B.; Mullen, S. P. (Psychology of Sport and Exercise, 2015)
Objectives: The purpose of this study was to create and provide validity evidence for the Processes of Change in Psychological Skills Training Questionnaire (PCPSTQ). Design: The current study used a cross-sectional research design. Methods: Five hundred fifty nine NCAA Division I, professional, and Olympic level athletes participated in the current study. To create the PCPSTQ, an initial pool of 114 items was generated by the research team. After a content validity process, 65 items were retained for analysis. Exploratory structural equation modeling was used as an analytic strategy to identify the most appropriate factor structure for the PCPSTQ. Decisions about the most appropriate model were made using multiple fit indices. To examine the construct validity of the PCPSTQ, a series of one-way ANOVAs were conducted to examine differences in processes of change use across stage of change. Results: In the current study, validity evidence provided support for a 7-factor process of change measure (?2 = 325.84, p < .001; Comparative Fit Index = .971; Tucker Lewis Index = .945; Root Mean Square Error of Approximation = .037; Standard Root Mean Square Residual = .020). Results also supported the construct validity of the scale as a significant difference in process of change use across stage of change was reported for all seven processes. Conclusions: Results of the current study support the factor structure and construct validity of the PCPSTQ. It appears that the processes of behavior change reported across multiple behavior change domains might also be viable for sport psychology professionals.